TOKSISITAS ISOLAT BACILLUS THURINGIENSIS YANG MENGANDUNG GEN CRY 1A TERHADAP HAMA PENGGEREK BATANG JAGUNG, OSTRINIA FURNACALIS GUENEE - Bahagawati, Bahagawati; Rizjaani, Habib; Sibuea, Agustina K. (JURNAL BIOLOGI INDONESIA, 2009)
ABSTRACTCry genes isolated from Bacillus thuringiensis produce crystal proteins that exhibit a highinsecticidal activity against several plant pests. The objectives of this experiment were todetect the presence of cry1A sequences from several local Bacillus thuringiensis isolatesmultiplied by Lep1A-Lep1B and Lep2A-Lep2B primers using PCR technique and to determinetheir toxicity against Ostrinia furnacalis, maize stemborer. From 59 tested isolates, 6 of themgave PCR products, two DNA bands, first was 490 bp, the expected size of Lep1A-Lep1Bprimers, and second was 986 bp, the expected size of Lep2A-Lep2B primers. These isolateswere Jtg 2151, 243, Cib 551, Lam 752, Lam 762 and C 522. All of tested isolates showedpotentially high toxicity against maize stemborer.Key words: B. thuringiensis, cry1A, Ostrinia furnacalis, PCR.Kata kunci: B. thuringiensis, cry1A, Ostrinia furnacalis, PCR.